Context-Specific Procedures for the Diagnosis of Human Schistosomiasis – A Mini Review - Hoekstra, Pytsje T.; van Dam, Govert J.; van Lieshout, Lisette (Frontiers in Tropical Diseases, 2021)
Schistosomiasis is a parasitic disease caused by trematode blood flukes of the genus Schistosoma, affecting over 250 million people mainly in the tropics. Clinically, the disease can present itself with acute symptoms, a stage which is relatively more common in naive travellers originating from non-endemic regions. It can also develop into chronic disease, with the outcome depending on the Schistosoma species involved, the duration and intensity of infection and several host-related factors. A range of diagnostic tests is available to determine Schistosoma infection, including microscopy, antibody detection, antigen detection using the Point-Of-Care Circulating Cathodic Antigen (POC-CCA) test and the Up-Converting Particle Lateral Flow Circulating Anodic Antigen (UCP-LF CAA) test, as well as Nucleic Acid Amplification Tests (NAATs) such as real-time PCR. In this mini review, we discuss these different diagnostic procedures and explore their most appropriate use in context-specific settings. With regard to endemic settings, diagnostic approaches are described based on their suitability for individual diagnosis, monitoring control programs, determining elimination as a public health problem and eventual interruption of transmission. For non-endemic settings, we summarize the most suitable diagnostic approaches for imported cases, either acute or chronic. Additionally, diagnostic options for disease-specific clinical presentations such as genital schistosomiasis and neuro-schistosomiasis are included. Finally, the specific role of diagnostic tests within research settings is described, including a controlled human schistosomiasis infection model and several clinical studies. In conclusion, context-specific settings have different requirements for a diagnostic test, stressing the importance of a well-considered decision of the most suitable diagnostic procedure.